Factors Influencing Consumers' Purchase Decision for Craft Beer Products - Yala, Sutas; Na Keeree, Pratsanee (Journal for Strategy and Enterprise Competitiveness, 2025)
This research aims to: 1) study the marketing mix factors that influence the decision to purchase craft beer, 2) study consumer behavior factors that influence the decision to purchase craft beer, and 3) study consumer attitude factors that influence the decision to purchase craft beer. A quantitative research method was employed using a questionnaire for data collection. The sample consisted of 400 individuals, including males, females, and LGBTQ+ people aged 20 years and above. Samples were selected using an online questionnaire distributed via QR codes to craft beer consumers both in craft beer shops and LINE groups. The data were analyzed using statistical methods, including frequency, percentage, mean, standard deviation, and multiple regression analysis. The results showed that: 1) marketing mix factors—product, price, and distribution—had a statistically significant relationship with the decision-making process in purchasing craft beer at the 0.05 significance level, whereas promotion had no significant effect; 2) consumer behavior factors—such as average frequency of craft beer consumption per month, average spending per purchase, tendency to try new craft beer products, and preferred purchase channels—significantly influenced the decision to purchase craft beer at the 0.05 significance level, while the main reason for purchasing craft beer, peak consumption period, purchase channel, information source, and the most influential person had no significant effect; and 3) consumer attitude factors—including the desire to try new products, the desire to enhance a sophisticated image, and beer-drinking experience or knowledge—had a statistically significant influence on the decision to purchase craft beer at the 0.05 significance level, while socializing or gathering had no significant influence.